A micropuncture study of the effect of parathyroid hormone on renal bicarbonate reabsorption. - Bank, N (1976)
Renal micropuncture and clearance experiments were carried out in rats to study the effect of parathyroid hormone (PTH) on renal tubular HCO-/3 reabsorption. The rats were studied during an initial period of parathyroid deficiency (acute thyroidparathyroidectomy, TPTX) and during infusion of large amounts of bovine PTH. Under normal acid-base conditions, PTH administration to TPTX rats caused a significant rise in proximal tubular fluid HCO-/3 concentration (TFHCO-/3), a decrease in fluid reabsorption, and a fall in proximal HCO-/3 reabsorption from 94.0 to 88.2% (P less than 0.01). In control experiments with mannitol infusion, a comparable reduction in proximal fluid reabsorption occurred without any significant effect on intraluminal HCO-/3 concentration. During acute intravenous HCO-/3 loading, PTH inhibited proximal HCO-/3 reabsorption. However, no change in whole kidney HCO-/3 reabsorption was observed in these experiments or in the animals studied under normal acid-base conditions. The findings are consistent with the view that PTH inhibits proximal tubular HCO-/3 reabsorption with normal or high filtered loads of HCO-/3, but distal segments of the nephron are able to reabsorb the excess delivered from the proximal tubule. Measurements of urinary ammonium and titratable acid indicate that net acid excretion (NH+/4 + TA -- HCO-/3) increases significantly after PTH administration. These results do not provide support for the view that PTH excess causes metabolic acidosis by reducing renal acid excretion.